Evaluation of Pump Discontinuation and Associated Factors in the T1D Exchange Clinic Registry. (March 2017) - Wong, Jenise C.; Boyle, Claire; DiMeglio, Linda A.; Mastrandrea, Lucy D.; Abel, Kimber-Lee; Cengiz, Eda; Cemeroglu, Pinar A.; Aleppo, Grazia; Largay, Joseph F.; Foster, Nicole C.; Beck, Roy W.; Adi, Saleh; et al.
Background: The objectives of this study were to examine factors associated with insulin pump discontinuation among children and adults followed longitudinally for 1 year in the multicenter T1D Exchange clinic registry, and to provide participant-reported reasons for stopping pump therapy. Methods: We longitudinally followed 8935 participants of all ages using an insulin pump at the time of registry enrollment. Logistic regressions were used to identify demographic and clinical factors associated with pump discontinuation. Pump discontinuation was self-reported by participants on a first annual follow-up survey. Results: The overall frequency of pump discontinuation was 3%. Discontinuation was higher in adolescents (4%) and young adults (4%) than in younger children (3%) or older adults (1%). In multivariate analysis of children between 6 and <13 and 13 and <18 years, participants who discontinued pump use were more likely to have higher HbA1c levels at baseline (adjusted P < .001 for both). The top participant-reported reasons for discontinuing the pump included problems with wearability (57%), disliking the pump or feeling anxious (44%), and problems with glycemic control (30%). Conclusions: In T1D Exchange registry participants, insulin pump discontinuation is uncommon, but more prevalent among adolescents and young adults, and youth with poor glycemic control. Given the known benefits of pump therapy, these populations should be targeted for support and education on troubleshooting pump use. Common reasons for discontinuation should also be considered in future device design and technological improvement.